The effect of the curing agent type on the flammability of butadiene-acrylonitrile rubbers - Janowska, G.; Rybiński, P.; Krauze, S. (Polimery, 2022)
The flammability of butadiene-acrylonitrile rubbers, containing 18 or 39 wt. % of AN (NBR 18 and NBR 39, respectively), has been investigated before and after curing with dicumyl peroxide, sulfur or iodoform. The oxygen index method (OI) (Table 1) and cone calorimetry (Table 2, Fig. 1-4) were applied. The toxicity of gaseous products of thermal decomposition and combustion of vulcanizates, described by the values of RTFHCO/CO2 (Table 3) and WLC50SM (Table 4) indices, has been evaluated.